Portfolio and Self-Assessment to Enhance Cultural (and Language) Awareness: A Case Study in a Translation Class - Harris Hermansyah Setiajid (Proceedings of ISELT FBS Universitas Negeri Padang, 2014)
Learner autonomies have become a major issue in the recent years. Learners are encouraged to undergo a cycle of learning, consisting of learning, experiencing, reflecting, and evaluating. Learner’s reflection has become an effective tool for students to measure their progress and to increase to what they have learned. The reflection can be made through portfolios and self-assessment method in which students are able to assess what they have done and to compare it with the teacher’s assessment. This will lead to students’ understanding of their problem and of weakness they do not realize previously. To some extent, the self-assessment method will also raise students’ awareness to what they have learned, and develop them to be autonomous learners, which are essential when dealing with real life tasks. In translation class, this cycle of learning and portfolios and learner self-assessment is beneficial for students in that they can reflect and assess how far they are progressing. Such method helps students to be an autonomous learner and solve the problems independently and enhance the cultural and language awareness. This paper tries to discuss a cycle of learning and to show how portfolios and learner self-assessment work in a translation class.